A factor analysis for the Spanish economy - Ángel Cuevas; Enrique M. Quilis (SERIEs - Journal of the Spanish Economic Association, 2012)
We present a medium-scale dynamic factor model to estimate and forecast the rate of growth of the Spanish economy in the very short term. The intermediate size of the model overcomes the serious specification problems associated with large scale-models and the implicit loss of information of small-scale models. The estimated common factor is used to forecast the gross domestic product by means of a transfer function model. Likewise, the model solves the operational and informational limits posed by the presence of an unbalanced panel of indicators and generates multivariate forecasts of the basic indicators.
Keywords: C22; C53; C82; E27; E32; 330; dynamic factor model; short-term economic analysis; Spanish economy; Kalman filter; transfer function; temporal disaggregation; forecasting; nowcasting; Wirtschaftswachstum; Prognoseverfahren; Faktorenanalyse; Aggregation; Zustandsraummodell; Spanien